Immune reactions to Listeria monocytogenes in the brain - Schlüter, Dirk; Buck, Christine; Reiter, Sabine; Meyer, Timothy; Hof, Herbert; Deckert-Schlüter, Martina (Immunobiology, 1999)
Listeria monocytogenes (LM) is a common pathogen of cerebral infections. Experimental studies in mice have revealed that epithelial cells of the choroid plexus, ependymal cells, macrophages/microglia, and neurons are the target cells of LM. For the intracerebral pathogenesis of LM cell-to-cell spread via phospholipase C was particularly important. However, phospholipase C-deficient LM were not completely attenuated and, therefore, other virulence factors may also contribute to the intracerebral spread of LM. In general, all mice suffering from cerebral listeriosis rapidly succumbed to the disease. Active systemic immunization prior to intracerebral infection reduced the mortality rate to 40%. The favorable prognosis of immunized mice correlated with a reduced intracerebral bacterial load, an increased recruitment of protective CD4+ and CD8+ T cells as well as an upregulated mRNA production of protective cytokines.